Serology and protein electrophoresis for evidence of exposure to 12 mink pathogens in free-ranging American mink (Neovison vison) in Argentina - Martino, Pablo Eduardo; Samartino, Luis Ernesto; Stanchi, Néstor Oscar; Radman, Nilda Esther; Parrado, Eduardo Joaquín (2018)
Background: Basic pathologic characteristics for farmed minks were previously reported worldwide. However, its status in the wild has not been studied in detail. Objective: Serology and electrophoresis were carried out for evidence of exposure to 12 mink pathogens on two different locations. Animals and methods: Serology was done in 87 wild minks by reference techniques against Toxoplasma gondii, Encephalitozoon cuniculi, Neospora caninum, Brucella abortus, Mycobacterium bovis, Leptospira interrogans, canine distemper virus (CDV), canine adenovirus (CAV), canine parvovirus (CPV), rabies virus (RV), Influenza A virus (FLUAV) and Aleutian disease virus (ADV). Hypergammaglobulinemia, the ADV main clinical feature, was determined by conventional electrophoresis. Results: Seventy-one percent of the 87 sera had antibodies against one or more pathogens. ADV accounted for the highest seroprevalence (29%), followed by T. gondii (26%), L. interrogans (14%), M. bovis (12%), B. abortus (9%), N. caninum (3%), CPV (3%) and CDV (2%). Seroprevalence was influenced by location but not sex or age. Additionally, 16% of the seropositive samples for ADV had gammaglobulin levels >40.0 g/L. Antibody titers for CDV and CPV were low and difficult to interpret as almost all these cases had borderline concentrations.